Longitudinal Effects of Self-Report Pubertal Timing and Menarcheal Age on Adolescent Psychological and Behavioral Outcomes in Female Youths from Northern Taiwan - Chih-Ting Lee; Meng-Che Tsai; Chung-Ying Lin; Carol Strong (Elsevier, 2017)
Early puberty is linked to adverse developmental outcomes in adolescents in Western societies. However, little is known about this relationship in an East Asian context. In addition, whether the impact of subjective pubertal timing (PT) and menarcheal age (MA) on adolescent psychosocial development persists into early adulthood remains unclear and is worthy of investigation. Methods: A subset of data was retrieved from the Taiwan Youth Project, which recruited and followed a longitudinal cohort of 7th- and 9th-grade female Taiwanese students from 2000 to 2007. Subjective PT was defined using the Pubertal Developmental Scale (PDS), which mainly measures pubertal changes. MA was recalled by participants themselves. Various psychological and behavioral factors were recorded and measured until the age of 20, including the use of alcohol and cigarettes, psychological well-being, sexual activity, and socially problematic behaviors. A χ2 test for linear-by-linear association and one-way analysis of variance followed by multivariate regression models were used to dissect the differential effects of PT and MA in the association with the outcome variables. Results: In total, 1545 female participants with an average age of 14.5 (±1.1) years were deemed valid for analysis. Among them, 257 (16.6%) participants perceived themselves as having early PT, defined as more than 1 standard deviation above the mean PDS score, and 82 (5.3%) had early MA (occurring before the 4th grade). In univariate analysis, participants with early PT had higher rates of smoking and sexual activity, and MA was not related to their psychobehavioral outcomes. After multivariate adjustment, only late PT was significantly correlated with lower amounts of cigarette smoking and sexual activity before the age of 20. Conclusion: Conceptual and actual pubertal developments may be differentially associated with psychobehavioral outcomes among young Taiwanese girls. Clinical attention should be given to adolescent self-perception of sexual maturation and developmental guidance provided accordingly.